Systemic low-grade inflammatory markers are associated with proximal spread of neuropathic symptoms - Zvonickova, K; Rhee, A; Sandy-Hindmarch, O; Furniss, D; Wiberg, A; Schmid, AB (Elsevier, 2024)
Neuropathic pain is a highly prevalent condition associated with persistent and severe disability. Some patients with neuropathic pain experience symptom spread outside neuroanatomical boundaries; these patients report more severe sensory symptoms and greater disability. However, the mechanisms behind such symptom spread are not fully understood. We used carpal tunnel syndrome (CTS) as a human model system of neuropathic pain to identify differences in the concentration of serologic inflammatory mediators among patients with CTS with territorial symptoms and those with proximal symptom spread to either the elbow or shoulder/neck. We conducted Quade ANCOVA’s, corrected for multiple testing, to compare the three groups in two independent cohorts: a discovery and validation cohort. The discovery CTS cohort (n=55; n=25 no spread, n=21 spread to elbow, n=9 spread to shoulder/neck) revealed higher serum concentrations of C-reactive protein (CRP) and interleukin-6 (IL-6) in patients with any symptom spread proximal to the wrist; interferon-g (IFN-g) was higher in patients with symptom spread to the elbow compared to those without proximal symptom spread. The validation study (n=72; n=34 no spread, n=16 spread to elbow, n=22 spread to shoulder/neck) replicated the association of higher CRP concentrations in patients with proximal spread to the elbow (no spread: median [IQR] 2.5 [5.4]; spread to elbow 6.2 [4.6]; spread to shoulder/neck 2.6 [3.7], p=0.006). No other markers replicated in the validation cohort. Our findings suggest that proximal symptom spread in the context of neuropathic symptoms is associated with low-grade inflammation. Funded in whole, or in part, by the Wellcome Trust [222101/Z/20/Z].